RECYCLING PET BOTTLES FOR ADDITIVE MANUFACTURING: A METHOD FOR 3D PRINTER FILAMENT PRODUCTION (Nigerian Journal of Technology, 2025)
Relevant technologies require reliable filaments from virgin materials and for exploration of waste PET bottles which simultaneously reduces environmental pollution associated with them. Desirable size, mechanical, chemical, thermal and physical properties of filaments are the significant determinants of their (filaments) respective applications and quality of products when in use on 3D printers. In this current work, an existing single screw extruder is modified to produce contaminant-free filament at various diameter from recycled polyethylene terephthalate (PET) for 3D printers. Flow rate test and tensile test were conducted to determine the mechanical properties of the filaments The V-PET, R-PET and R-PETG samples were fabricated with a gauge length of 50mm, and a tensile test was performed on each specimen. A weight proportion method was used to add an additive to the recyclable waste which yielded a good result in the by-product mechanical properties with a tensile strength up to 42MPa.  A weight ratio of 1:4 (EG:V-PET) resulted in the least melting temperature with the least extrusion time in the case of V-PET. Increasing the reaction temperature in R-PET leads to an increase in melting time that results in an increase in total extrusion time. An experiment conducted in this study found that the extrusion time required for R-PET was reduced from 120 seconds to 80 seconds at 75% conversion rate.